La font bizantina d’un passatge del Tirant: l’episodi del filòsof calabrès al capítol cx - Jordi Redondo (Tirant, 2012)
This paper revisites the theme of the sources of Tirant’s chapter cx, for which a highly probable origin depending on a folkloric tale has been suggested (Beltrán Llavador 2006). The author fosters a concrete source, the didactic Greek narrative poem entitled Ptokholeon, and bases his proposal on the intertextual analysis, both of subjects and of linguistic borrowings as well.